Geographical Variation among the Tharu of Lumbini Province - Rai, Tara Mani; Rai, Diwas (Bhashalok भाषालोक, 2026)
This study examines the lexicostatistical and phonetic analysis of Tharu varieties spoken in Lumbini Province, Nepal. The study seeks to delineate the linguistic links and evaluate mutual intelligibility among four varieties: Dangouriya, Deukhuriya, Desouriya, and Nawalpuriya. Using a list of 210 words, data were gathered through elicitation from native speakers. The computer software COG was used to look at lexical and phonetic variation. The findings reveal that Dangouriya, Deukhuriya, and Desouriya form a core dialect cluster where phonetic similarity is from 75 to 80 percent and moderate to high lexical overlap is from 64 to 71 percent. To the contrary, Nawalpuriya emerges as a peripheral variety, showing lower lexical similarity scores from 41 to 44 percent and phonetic scores from 62 to 63 percent. This divergence suggests the influence of geographical isolation and external language contact. The pattern of phonological stability among core varieties that have lexical divergence is shaped by sociocultural factors and geographical distribution. This study contributes to identifying geographical variation and making the language policy and planning, as the Tharu language is already recommended for the provincial language in Lumbini by the Language Commission.